2020
DOI: 10.1007/s40620-020-00799-w
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of bilirubin and bile acids with intermittent coupled plasmafiltration and adsorption in liver failure (HERCOLE study)

Abstract: Background CPFA is an extracorporeal treatment used in severe sepsis to remove circulating proinflammatory cytokines. Limited evidence exists on the effectiveness of bilirubin adsorption by the hydrophobic styrenic resin, the distinctive part of CPFA. The aim of this study is to validate CPFA effectiveness in liver detoxification. Methods In this prospective observational study, we enrolled patients with acute or acute-on-chronic liver failure (ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
0
12
0
3
Order By: Relevance
“…[7] Various studies have shown that besides effectively removing water-soluble and protein binding toxins, CPFA can also reduce bilirubin levels by 30% to 50% in each cycle. [57][58] The HERCOLE study [59] showed that CPFA was effective in the "detoxification" of patients with liver failure and is now considered a good "bridging technique" to liver transplantation or until recovery of baseline liver function. The regional citrate assisted anticoagulation mode and corresponding protocol monitoring (Table 2) provided by Amplya TM allow the safe use of CPFA under these clinical conditions.…”
Section: Liver Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Various studies have shown that besides effectively removing water-soluble and protein binding toxins, CPFA can also reduce bilirubin levels by 30% to 50% in each cycle. [57][58] The HERCOLE study [59] showed that CPFA was effective in the "detoxification" of patients with liver failure and is now considered a good "bridging technique" to liver transplantation or until recovery of baseline liver function. The regional citrate assisted anticoagulation mode and corresponding protocol monitoring (Table 2) provided by Amplya TM allow the safe use of CPFA under these clinical conditions.…”
Section: Liver Dysfunctionmentioning
confidence: 99%
“…The regional citrate assisted anticoagulation mode and corresponding protocol monitoring (Table 2) provided by Amplya TM allow the safe use of CPFA under these clinical conditions. [32,59] Sodium, potassium, chlorine, magnesium (*) In the "free citrate" mode, the management of citrate and calcium solution is controlled by the operator. The machine does not monitor or adjust any parameters related to anticoagulation, and the treatment team needs to perform protocol monitoring and control.…”
Section: Liver Dysfunctionmentioning
confidence: 99%
“…A recent trial, the HERCOLE study, demonstrated the feasibility and practicality of applying CPFA in patients with liver failure. 89 Importantly, liver failure per se is not a contraindication for regional citrate anticoagulation (RCA) since citrate metabolization also takes place in the myocytes and the renal cortex, [90][91][92][93] in both CPFA and PAP citrate can be used. 94 A retrospective analysis compared the bilirubin removal capacity of PAP versus MARS.…”
Section: Pl a S Ma Adsorp Ti On Perfus I Onmentioning
confidence: 99%
“…The evidence for plasma exchange is rather limited and a clinical benefit is in question. Liver dialysis can reduce serum bilirubin and bile acid concentrations (25), however, it is unclear if some bile acid species might be required for liver regeneration. Thus, liver dialysis may on the one hand remove harmful bile acids while on the other hand also reducing signals for regeneration.…”
Section: Is Fibrosis Necessary For Liver Regeneration?mentioning
confidence: 99%